Hg 0 capture over MoS2 nanosheets containing adsorbent: effects of temperature, space velocity, and other gas species - Zhao, Haitao; Yang, Gang; Mu, Xueliang; Cao, Pengfei; Gao, Xiang; Wu, Tao (Elsevier, 2017)
Fossil fuel burning is the largest anthropogenic source of mercury emission, which is expected to be the first industrial sector to be addressed under Minamata Convention. In this research, the preliminary investigation has been carried out to understand the effects of temperature, space velocity, and SO2 and O2 on Hg0 capture over MoS2 nanosheets containing elemental mercury adsorbent. The adsorbent exhibited excellent performance in the removal of Hg0 at a low temperature below 125°C (particularly at 50°C) with a space velocity below 9.0×104 ml/(h·g). It was found that the presence of O2 had positive effect on Hg0 removal whilst SO2 had slightly negative effect on mercury capture at low temperature, such as 50°C. However, such negative effect became negligible when O2 co-existed with SO2 in the simulated flue gas. The research provided fundamental information for further development of the 2D graphene-like MoS2 nanosheets containing adsorbent for mercury capture.